Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Renyar

  • 4 years ago

Solve 3 log6 2 + 2 log6 3 – log6 x = 2

  • This Question is Closed
  1. lgbasallote
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    probably the best first thing to do is to condense the equation. You know how right?

  2. ezhyl_marie
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    log6 8 + log6 9 = log6 36 + log6 x log6 (8*9) = log6 (36x) log6 72 = log6 36x 72=36x x=2 bye

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy